A Review on Canine and Feline Prostate Pathology - Palmieri, Chiara; Fonseca-Alves, Carlos Eduardo; Laufer-Amorim, Renee (Frontiers in Veterinary Science, 2022)
Prostatic diseases are very common in male dogs, accounting for 3-10% of cases submitted to the veterinary practitioners. Commonly reported canine prostatic disorders include prostatic hyperplasia, prostatitis, prostatic cysts and prostatic carcinoma. However, clinical signs may be nonspecific, or many cases are asymptomatic, thus leading to a difficult estimation of the actual prevalence of clinical cases. On the other side, because of the rare occurrence of prostate disease in cats, very little is known about pathogenesis, diagnostic approaches and treatment. The goal of this review is to provide detailed clinical and pathological overview of the feline and canine prostatic pathology, including the most up-to-date classification systems and histological findings. Emphasis is places on gross, cytological and histological features that are critical to reach a definitive diagnosis for a proper treatment and prognosis.